2009
DOI: 10.1186/1471-2458-9-187
|View full text |Cite
|
Sign up to set email alerts
|

Improved salt iodation methods for small-scale salt producers in low-resource settings in Tanzania

Abstract: Background: Universal salt iodation will prevent iodine deficiency disorders (IDD). Globally, salt-iodation technologies mostly target large and medium-scale salt-producers. Since most producers in low-income countries are small-scale, we examined and improved the performance of hand and knapsack-sprayers used locally in Tanzania.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 8 publications
0
15
0
1
Order By: Relevance
“…Sustaining this success, however, continue to be a significant challenge as it needs close cooperation among partners at various levels and active monitoring with small-scale salt producers. [32][33][34] In some countries where the fortification of iodine is mandatory, the incidence of excessive iodine consumption among school-aged children has increased. 6,17,35,36 This increase is significant and needs strengthening of monitoring systems in Iodine Deficiency control programs, such as adjusting iodine concentration in fortified salt.…”
Section: Discussionmentioning
confidence: 99%
“…Sustaining this success, however, continue to be a significant challenge as it needs close cooperation among partners at various levels and active monitoring with small-scale salt producers. [32][33][34] In some countries where the fortification of iodine is mandatory, the incidence of excessive iodine consumption among school-aged children has increased. 6,17,35,36 This increase is significant and needs strengthening of monitoring systems in Iodine Deficiency control programs, such as adjusting iodine concentration in fortified salt.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, an attempt has also been made with production-end interventions to nudge salt manufacturers away from unrefined and unpackaged salt production to refined and packaged salt. Assey et al have shown that knap-sack spraying and manual mixing yielded much more homogeneous iodisation of salt in salt bags at small-scale salt producers (27) . Several projects have been undertaken to supply packaging material to small-and medium-scale producers, to support them for technology upgrading and setting up of refineries (28) .…”
Section: Discussionmentioning
confidence: 99%
“…In many areas weaknesses in salt quality assurance in salt production that include inconsistencies in salt/iodate mixing, consumer's preference for uncontrolled backyard salt production, and non-adherence to salt regulations by salt producers and traders are reflected in low coverage of I-salt and in the high or low levels of iodine [ 11 , 25 ]. The coverage of I-salt at household level obtained using test kit method in this study and in our previous study [ 14 ] showed its concordance with UIC.…”
Section: Discussionmentioning
confidence: 99%
“…The difficulty of providing a continuous supply of potassium iodate and the poor iodation technologies in many small-scale salt producers could be factors in the shortage of I-salt in households and the iodine variability observed in this survey [ 14 , 27 ]. Increased use of appropriate technology from recently modified iodation procedures using local spray pumps with manual mixing under close supervision [ 25 ], and the creation of a system for consumers to contribute to the costs of potassium iodate may reverse the situation and sustain salt iodation in Tanzania.…”
Section: Discussionmentioning
confidence: 99%